Owen and Sassoon Reconsidered - Cristina Pividori (Tiempo Devorado)
Poetry, alongside other artistic and scholarly work, has played an invaluable role in preserving the traumatic memory of the First World War, especially after the passing of the last known veteran marked the end of the era of living witnesses to the conflict. The centenary of the Great War (2014-2018) has sparked a renewed poetic output, leading to the publication of anthologies like Poet Laureate Carol Ann Duffy’s 1914: Poetry Remembers (2013). This edited collection includes two poems by the canonical British soldier-poets Wilfred Owen and Siegfried Sassoon: “The Send-Off” and “Survivors.” Contemporary poets Carol Ann Duffy and Jackie Kay have selected these poems and have contributed their own pieces in response. Based on two theoretical frameworks, Jan and Aleida Assmann’s notion of “cultural memory” developed in the 1980s and 1990s and Marianne Hirsch’s concept of “postmemory” (2008), I will explore the intertextual references, thematic parallels, allusions and motifs that link the contemporary poems with those of Owen and Sassoon to study how memories, post-memories and aesthetic recreations of conflict interact and transform one another, highlighting the complexity and contingency of historical knowledge. I claim that the First World War has served as a foundational narrative that has been reinterpreted to address contemporary concerns and sensibilities and that the interaction between contemporary and World War One poetry reveals not only the enduring impact of transgenerational trauma and cultural memory on the disruption and transformation of individual and collective identities, but also the idea that the interpretation of conflict through post-lenses transcends specific historical backgrounds.